Test of the Inhibitory Power of Durian Leaves (Durio zybethinus) Against the Growth of the Fungus Malassezia furfur: Uji Daya Hambat Daun Durian (Durio zybethinus) Terhadap Pertumbuhan Jamur Malassezia furfur - Khusnul Fahima, Aufiq; Islawati , Islawati; Asnidar, Asnidar (FASKES : Jurnal Farmasi, Kesehatan, dan Sains, 2023)
Background:. Natural treatment of Pityriasis versicolor (Panu) disease by the public generally uses leaves, one of which is to use durian leaves which have benefits as antifungal in the genus candida, antibacterial and anesthetic. One of the durian leaf compounds that are anti-fungal is Saponin Compounds. Objektives: The purpose of the study was to determine the most effective inhibitory power of durian leaf extract (Durio zybethinus) against the growth of Malassezia furfur fungus. Methods: The research method used in this study is an experimental laboratory, using a pseudo-experimental design design. Results: The results of this study showed that durian leaves can inhibit the growth of Malassezia furfur fungus with strong categories at concentrations of 60%, 80%, 100% and positive controls. Conclusions and suggestions: Of the 3 variations in concentrations of 60%, 80%  and 100% that have been used to measure the inhibitory zone assisted in the media, the results were 22.1 mm, 24 mm, and 25.5 mm respectively and among all variations, the most effective variation was at 100% concentration and positive control.